Colour changes and equilibrium moisture content on thermomechanical densified wood - CARVALHO,DOUGLAS E. (2021)
Abstract Color change associated with significative positive improve in physical properties is a challenge in wood research. This study investigated the changes in the color of the Gmelina arborea wood which underwent a thermomechanical densification process. The process was performed by applying three different temperatures (140 °C, 160 °C and 180 °C) with thickness reduction of 20% and 40% using 2.5 MPa equivalent pressure. The color change of the pieces was analyzed through the CIEL * a * b * system. The relationship between the color and the equilibrium moisture content of the densified material was also analyzed. The process reduced the lightness and yellow hue of the wood, with increased red pigment resulting in darker coloration of the treated pieces. The higher temperature used resulted in more significant changes in wood tone and lower equilibrium moisture. The process proved to be effective to change the color and significantly reduce the equilibrium moisture content in wood samples where the density was increase by 20% and 50% compared to natural wood.